2018
DOI: 10.4103/ijn.ijn_15_18
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hemodialysis on corrected QT interval and QTc dispersion

Abstract: Hemodialysis patients are at higher risk of cardiovascular disease due to traditional and dialysis-related risk factors. Our aim was to study the effects of hemodialysis on the corrected QT interval (QTc) and QTc dispersion in chronic kidney disease (CKD) without clinically manifest heart disease. Two hundred cases of CKD on chronic intermittent hemodialysis of >3 months' duration were included in the study. Twelve-lead electrocardiography and samples for serum creatinine, potassium, calcium, and magnesium wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 15 publications
(16 reference statements)
0
6
0
Order By: Relevance
“…Although the mechanism of QT and QTd prolongation after COVID‐19 recovery is not fully known, the possible mechanism in hemodialysis patients may be due to fibrosis and conduction variability that occurred in the myocardium at the cellular level after healing of the infection. In hemodialysis patients, some QT prolongation is expected as a result of the long‐term effects of uremia on the myocardium [25]. In our study, the prolongation in repolarization parameters may result from the combined effects of both uremia and infection.…”
Section: Discussionmentioning
confidence: 71%
“…Although the mechanism of QT and QTd prolongation after COVID‐19 recovery is not fully known, the possible mechanism in hemodialysis patients may be due to fibrosis and conduction variability that occurred in the myocardium at the cellular level after healing of the infection. In hemodialysis patients, some QT prolongation is expected as a result of the long‐term effects of uremia on the myocardium [25]. In our study, the prolongation in repolarization parameters may result from the combined effects of both uremia and infection.…”
Section: Discussionmentioning
confidence: 71%
“…We and other colleagues previously found that chronic kidney disease was associated with prolonged QTc interval ( 38 40 ). Similar with ECG-LVH, the combination of chronic kidney disease and QTc prolongation resulted in a higher risk of mortality compared with either condition alone ( 39 ).…”
Section: Discussionmentioning
confidence: 78%
“…45,46 Local and systemic effects are produced by PQ toxicity, which damages multiple tissues and organs in humans 47 and animals. 48,49 The most considerable damage happens to the lung tissue 50,51 owing to the accumulation and uptake of Paraquat by lung tissue. 30 The Paraquat poisoning pulmonary manifestations start with diffuse consolidation after several days into cystic lesions after focal fibrotic lesions with extensively higher mortality.…”
Section: Resultsmentioning
confidence: 99%